2018
DOI: 10.1021/acsomega.8b00987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molten Salt Synthesis Processing Duration on the Photo- and Radioluminescence of UV-, Visible-, and X-ray-Excitable La2Hf2O7:Eu3+ Nanoparticles

Abstract: Ln 3+ -ion-doped nanomaterials possess excellent properties because of their high color purity, longer excited state lifetime, narrow emission, and large Stokes shifts. In this work, we studied the correlation between the luminescence properties of La 2 Hf 2 O 7 :Eu 3+ pyrochlore nanoparticles (NPs) synthesized by a molten salt synthesis (MSS) method at a relatively low temperature and several MSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 66 publications
0
33
0
Order By: Relevance
“…The photophysical properties of luminescent Eu 3+ ions are strongly governed by the local environment, which depends on the crystal field surrounding the emitting ion. In our earlier work, we focused on separate exploration of the effect of Eu 3+ doping concentration, effect of molten salt processing time, effect annealing temperature, effect of co‐precipitating pH on the emission output, quantum efficiency, radioluminescence output and excited state lifetime of La 2 Zr 2 O 7 and La 2 Hf 2 O 7 NPs . Molten salt synthesis has several advantages for an unique materials synthesis method, such as low formation temperature, environment benignness, simple to operate in normal research laboratory, easy to scale up, and cost efficient .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The photophysical properties of luminescent Eu 3+ ions are strongly governed by the local environment, which depends on the crystal field surrounding the emitting ion. In our earlier work, we focused on separate exploration of the effect of Eu 3+ doping concentration, effect of molten salt processing time, effect annealing temperature, effect of co‐precipitating pH on the emission output, quantum efficiency, radioluminescence output and excited state lifetime of La 2 Zr 2 O 7 and La 2 Hf 2 O 7 NPs . Molten salt synthesis has several advantages for an unique materials synthesis method, such as low formation temperature, environment benignness, simple to operate in normal research laboratory, easy to scale up, and cost efficient .…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier work, we focused on separate exploration of the effect of Eu 3+ doping concentration, effect of molten salt processing time, effect annealing temperature, effect of co-precipitating pH on the emission output, quantum efficiency, radioluminescence output and excited state lifetime of La 2 Zr 2 O 7 and La 2 Hf 2 O 7 NPs. 11,12,[36][37][38][39] Molten salt synthesis has several advantages for an unique materials synthesis method, such as low formation temperature, environment benignness, simple to operate in normal research laboratory, easy to scale up, and cost efficient. 40 From these studies, we found that the La 2 Hf 2 O 7 -based NPs display better luminescence and scintillation performance compared to the La 2 Zr 2 O 7 NPs, but could not understand the underlying reasons for their luminescence differences.…”
Section: Introductionmentioning
confidence: 99%
“…We also want to emphasize here that photophysical properties of pristine LHOE powder NPs published before [5,7,21] looks very similar to that of film in terms of emission bandwidth and asymmetry ratio. Only difference is increase in stark component of MDT to 3 in film compared 2 in pristine powder.…”
Section: Excitation and Emission Spectra Of The Lhoe-pvdf Films And Fmentioning
confidence: 80%
“…Some of the favorable properties include excellent dielectric properties due to its small number of defect densities, ability to accommodate large concentration of dopant both at A and B sites with a general formula of A 2 B 2 O 7 , wide bandgap, moderate phonon E = 745 cm −1 and high stopping power for X-and γ-rays with Z Hf = 72, and high density of 7.9 g/cm 3 . [19][20][21] We have done extensive work on red-emitting La 2 Hf 2 O 7 :Eu 3+ (LHOE) down-converting nanoparticle (NP) powders for several applications in the areas of phosphors, scintillators, thermographic phosphors, etc. [5,7,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation